1981
DOI: 10.1080/01651269.1981.10553421
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of egg envelopes in harvestmen (Chelicerata, Opiliones)

Abstract: Ultrastructural studies of egg envelopes in four species of harvestmen have shown that a spongy vitelline envelope secreted by the oocyte appears on the oocyte surface at the beginning of vitellogenesis. As the oocytes grow, characteristic changes in the thickness and structure of the vitelline envelope can be observed. The homogeneous vitelline envelopes of eggs located inside the uterus are coated with a layer of loose, foamy material. The vitelline envelopes of laid eggs are covered only with mucus which bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In the investigated stonefly ovaries, secretion of eggshells starts relatively early. Similarly, early deposition of egg envelopes has been described in myriapods, crustaceans and arachnids (Nørrevang 1972; Herbaut 1974; Witaliński and Żuwała 1981; Witaliński 1993; Ikuta et al . 1997).…”
Section: Discussionmentioning
confidence: 63%
“…In the investigated stonefly ovaries, secretion of eggshells starts relatively early. Similarly, early deposition of egg envelopes has been described in myriapods, crustaceans and arachnids (Nørrevang 1972; Herbaut 1974; Witaliński and Żuwała 1981; Witaliński 1993; Ikuta et al . 1997).…”
Section: Discussionmentioning
confidence: 63%
“…barbarus, seems to support this supposition. In harvestmen (Opiliones), the vitelline envelope lacks channels but has a spongy structure and is easily permeable (Witalinski and Zuwala, 1981). In the mite Hafenrefferia gilvipes (Oribatida), the vitelline envelope is also devoid of perforations but has a granular rather than compact structure (Witalinski, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…These segmental adhesions are composed of a substance, which is different from the spherical scaffolds that maintains its shape for a long time. According to Witaliński and Žuwała (1981) and Makover et al (2019), the oviposition uid contains mucus and low-molecular-weight proteins. The lowmolecular-weight proteins indicates the basic spherical units of CM, while mucus forms the adhesion between the units.…”
Section: Discussionmentioning
confidence: 99%
“…Hadley (1978) con rmed the presence of a lipid layer impermeable to water on the egg surface. Witaliński and Žuwała (1981) suggested that the mucus-containing oviposition uid coats the chorion, causing aggregation of eggs. Conti et al (2015) suggested that the aggregation of the eggs restricts their dehydration, as they become tightly attached to each other.…”
Section: Introductionmentioning
confidence: 99%